Mechanical ventilation in Guillain–Barré syndrome. (1st November 2020) - Shang, Pei; Zhu, Mingqin; Baker, Matthew; Feng, Jiachun; Zhou, Chunkui; Zhang, Hong-Liang
ABSTRACT: Introduction : Up to 30% of patients with Guillain– Barré syndrome (GBS) develop respiratory failure requiring intensive care unit (ICU) admission and mechanical ventilation. Progressive weakness of the respiratory muscles is the leading cause of acute respiratory distress and respiratory failure with hypoxia and/or hypercarbia. Bulbar weakness may compromise airway patency and predispose patients to aspiration pneumonia. Areas covered : Clinical questions related to the use of mechanical ventilation include but are not limited to: When to start? Invasive or noninvasive? When to wean from mechanical ventilation? When to perform tracheostomy? How to manage complications of GBS in the ICU including nosocomial infection, ventilator-associated pneumonia, and ICU-acquired weakness? In this narrative review, the authors summarize the up-to-date knowledge of the incidence, pathophysiology, evaluation, and general management of respiratory failure in GBS. Expert opinion : Respiratory failure in GBS merits more attention from caregivers. Emergency intubation may lead to life-threatening complications. Appropriate methods and time point of intubation and weaning, an early tracheostomy, and predictive prophylaxis of complications benefit patients' long-term prognosis.